Parental relationships, emotion regulation and orthorexia: A study on adolescent athletes - Giulio D$1 (BUrso s; Andrea Maynard
Background: This study seeks to further our understanding of the factors associated with adolescent athletes and disordered eating, by expanding current research into a less-explored eating disorder known as orthorexia. Aim: The aim of the study is to explore the impact of parents$1 (Brelationships and emotional regulation on the orthorexia nervosa (ON) tendencies of adolescent athletes. Methods: The participants were 303 adolescents, ranging from 15 to 17 years old, of which 139 participated in competitive sport, and 164 did not. Three self-report questionnaires were administered to assess orthorexia (ORTO-15), relationship with parents (Inventory of Parent and Peer Attachment) and emotion regulation (Emotion Regulation Questionnaire). Results: The results highlight that those who practice sports report higher levels of orthorexia, inadequate relationships with parents, as well as greater emotional regulation difficulties. Furthermore, inadequate parents$1 (Brelationship predicts orthorexia while expressive emotional regulation mediates this relationship. Conclusion: These findings highlight how ON tendencies in athletes are linked to poor management of emotions combined with inadequate relationships with parents in terms of communication and affection. Implications for practice and support for athletes are discussed.s